Analysis of the Conditions of Legitimate Defense (self-defense) in Iranian Criminal Law, with Emphasis on Judicial Procedure - Ahmad Javidi; Seyed Mahmoud Majidi; Mohamad Javad Baghi zadeh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Legitimate defense (self-defense) is one of the justifiable causes of crime. When a person commits a crime to defend the life, honor, property, and freedom of self or anyone else, the crime would not be prosecutable in the case of the community of defense conditions. The judicial procedure has an underlying position, along with law, legal doctrine, and other legal references. Due to the necessity of interpreting general regulations of legitimate defense and meeting their ambiguities, it is necessary to obtain the judicial procedure in this case. In this study, some votes issued by the General Board or branches of the Supreme Court are used to investigate the conditions of self-defense in judicial procedure and are divided into three general sections. In the first section, the conditions of self-defense are discussed in the Iranian Penal Code and judiciary to meet their ambiguities. In the second section, legal perceptions on the cases of accepting claims on self-defense in the judiciary are discussed. The third section discusses the rejection of a claim on self-defense in the judicial procedure. The judicial procedure before the revolution used to change the death penalty into life imprisonment or temporary imprisonment on lack of observance of conditions of defense resulting in murder on behalf of the defender in case of presence of mitigation directions. After the revolution, in case of authentication of the principle of defense and lack of proportionality and silence of law, the defender is charged to pay the blood-money due to the credited sentences. In case of lack of authentication of the principle of defense, the aggressor is sentenced to retaliation.